Statistical implications of the pick technique in a basketball match performance analysis - Izzo, R.; Varde'i, C. H.; Righi, E.; Cejudo, A.; Giovannelli, M. (Journal of Physical Education and Sport, 2023)
The science of sport applied to basketball has a rather long history, the first studies started at the end of the sixties and the beginning of the seventies (Beals et al. 1971), and over the years especially in the United States, due to the NBA phenomenon, the application of science and of statistics in performance analysis has increasingly taken hold. The analysis on the court, described by this study through video analysis and statistics, is based on the attempt to establish within some elite matches, the real effectiveness, statistically proven, of the technical element of the pick, which today characterizes most of the attacks in Italian Serie A basketball championship, and worldwide too, investigating the most common ones. Basically, the work done deals with the impact on the performance of the picking technique in basketball, taking into consideration the most common pick techniques in elite basketball such as the "Pick and roll, the vertical pick, the horizontal pick, the stagger and the double high pick and roll". The mathematical/statistical representation of the data obtained will help to the project hypotheses. From the results obtained from our study, it`s clear that pick and roll is therefore the most used precisely because it`s the pick that creates greater difficulty on defense, especially when it creates a "mismatch" (different physical and technical types of athletes facing each other). The successful Pick and Rolls are on average 20 per game and have a standard deviation of 6 so for 68% of the cases the Pick and Roll vary from 14 to 26.